2021
DOI: 10.1088/1757-899x/1114/1/012098
|View full text |Cite
|
Sign up to set email alerts
|

Physical, optical and structural characterizations of Dy3+-doped lead borate glasses

Abstract: In the current studies optical, physical and structural properties of rare-earth doped borate glasses have been reported. Bulk samples were prepared by using melt quenching technique with nominal composition 70B2O3-(17-x)ZnO-10PbF2-3Na2O-xDyF3 and 60B2O3-(27-x)ZnO-10PbF2-3Na2O-xDyF3, where (x=0,1). XRD analysis was used to confirm the amorphous nature of prepared samples. Optical and structural properties of as prepared samples were studied using UV-Visible and FTIR absorption spectra. The undoped and doped gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…A high value of E 0 in this composite, suggests that weak bonds have been converted into defects within this material, emphasizing the presence 12 The tan δ as a function of temperature at different frequencies ranging from 1 to 100 kHz for the present transparent composite sample Fig. 13 The optical spectrum of the present transparent composite sample at room temperature of structural disorder and defects that impact its properties [47].…”
Section: Optical and Ferroelectric Studiesmentioning
confidence: 71%
See 2 more Smart Citations
“…A high value of E 0 in this composite, suggests that weak bonds have been converted into defects within this material, emphasizing the presence 12 The tan δ as a function of temperature at different frequencies ranging from 1 to 100 kHz for the present transparent composite sample Fig. 13 The optical spectrum of the present transparent composite sample at room temperature of structural disorder and defects that impact its properties [47].…”
Section: Optical and Ferroelectric Studiesmentioning
confidence: 71%
“…Figure 15 displays the polarization versus electric field (P-E) of the present composite sample at various electric field. It is observed that the P-E loops at low electric field (10,11,13, and 14 kV/cm) exhibit double hysteresis loops, as well as an almost linear P-E relationship in the middle section of the hysteresis loop. The double hysteresis loops in the present composite sample could be explained by the presence of random local strain and defect dipoles in the ferroelectric of BaTiO 3 lattice [49][50][51].…”
Section: Optical and Ferroelectric Studiesmentioning
confidence: 96%
See 1 more Smart Citation